STUDI KOMPARATIF KONSEP VEGETARIAN DALAM SUDUT PANDANG THERAVĀDA DAN MAHĀYANA - Suwito Suwito (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2021)
This research examines the comparative study of the vegetarian concept from the Theravada and Mahayana point of view. Background of this research In today's modern era there are many views that have been developed, such as views on food. but many people misunderstand in interpreting someone who runs Vegetarian. Buddhism itself has several prominent sects of which the two major sects are Theravada and Mahāyana. The two sects belong to Buddhism but have different ways of achieving the highest happiness, as is the case with vegetarianism. However, this does not make the two views of Buddhism hostile, but these two views make people aware of the differences in the history of the formation of vegetarian views from each sect. The Theravāda view itself places more emphasis on attaining Nibbanaan while the Mahāyana focuses more on loving-kindness.